MODIFIED VARIATIONAL ITERATION METHOD FOR STRAIGHT FINS WITH TEMPERATURE DEPENDENT THERMAL CONDUCTIVITY - İnç, Mustafa; Khan, Hasib; Baleanu, Dumitru; Khan, Aziz (Vinca Inst Nuclear Sci, 2018)
The modified variational iteration method (MVIM) has been used to calculate the efficiency of straight fins with temperature dependent thermal conductivity. The obtained results are compared with homotopy analysis method (HAM), homotopy perturbation method (HPM), and Adomian decomposition method (ADM). It is used w # 0 auxiliary parameter to keep under control convergence region of solution series in MVIM. As a result, although MVIM and HAM give results close to each other; HPM and ADM give divergent results from analytical solution.
Keywords: modified variational iteration method; thermal conductivity; series solution